Knowledge diversity and healing practices of traditional medicine in Nepal. (2016)
SUMMARY: Background: Traditional medicine is widely used in treatment, diagnosis, prevention, cure, and management of many health problems. Globally, traditional medicines are easily accessible, assessable, acceptable, available and affordable. Many people wished to cure their diseases by opting alternative medicine. Traditional medicine can be defined as culturally and regionally specific body of knowledge developed by local and indigenous communities over period of time in response to the need of their specific local treatment. Scientists believe that the relationship between human beings and environment contribute to establish a strong foundation for the organization of indigenous knowledge. The primary objectives of this research are to assess the present situation of practices of indigenous medical knowledge and its resources. In addition, the study has also aimed to discover the methods/ technique to manage common ailments by the traditional healers. Methods: It was cross-sectional study. The research team used both quantitative and qualitative method. For the Central Development Region, both the qualitative and quantitative methods were used. For the Western Development Region, the team used qualitative method to conduct the study between November 2014 and June 2015. Likewise, the team also used qualitative method for Eastern, Midwestern, and Far-western Development Regions for collecting data from September 2015 to June 2016. Demographic information, professional information, knowledge and practices, herbs and herbal compositions etc. were gathered by close-ended questions. Whereas, the name of the diseases those healers are treating, medicinal plants they used, diagnosis process, and treatment process were asked with open-ended questions. The total participants were 139 (ten participantss from each districts except Dadeldhura which was 9) i.e. 50 from Western Development Region, 30 from Eastern Development Region, 30 from Mid-western Development Region and 29 from Far-western Development Region. For the Central Region, 30 VDCs were selected by probability proportionate from 19 districts and total sample sizes were 511. Quantitative method was used to measure a certain domain like sex, the age of patient, educational status of respondent in this region. Interviews were analyzed using deductive and inductive content analysis. Information related to knowledge and practice was assessed using semi-structured or predetermined thematic areas and later finalized by the constant comparative method, whereas information related to perception and attitude toward the profession were coded with keyword approach, formed categories and finalized the appropriate theme. Results: Majority of the traditional healers had the title like Baba, Baidhya, Baje, Bijuwa, Dhami, Doctorni, Guruma, Guruwa, Hakkim, Lama, Mata, Tantrik, Jadibuti Gyata, Fukfake, Pandit, Lama, Shoka, Jhakri, Jyotishi and Moulana. Majority of participants answered that they learnt the healing practices from their 'Forefather' and 'Guru'. Very few numbers of participants had formal education on traditional medicine. The daily footfalls of people having health problems significantly varied according to the time, day, season and 'Tithi Miti' (Lunar calendar date). Traditional healers were prescribed with medications and suggested for worshiping specific gods, chanting mantras and sacrificing animals by different processes like 'Jokhana Herney', 'Dhyangro Bajaune', 'Akhet Herne', etc. Most frequently used medications were ayurvedic medical products, medicinal plants, minerals and certain animal products. Traditional healers were accepting the treatment cost rather than consultation fees. They charged money in case of making 'Buti' (Amulet). Traditional healers claimed that they were treating different types of diseases like child diseases like diarrhea, bloody diarrhea, dysentery, pneumonia, runche (crying), infection of cord, etc. Female health problems like menstrual irregularities, dysmenorrhea, infertility, family planning problems, pregnancy complications, etc. Similarly, all other types of illnesses and sicknesses like fever, stomach pain, wound, jaundice, psychological issues and sinusitis, epilepsy, bloody diarrhea, dog's bite, poison cases, tuberculosis, leprosy, diarrhea, gastritis, asthma, stone, gastritis, pneumonia, headache, dizziness, limbs ache, paralysis, etc. Traditional healers used more than 200 medicinal plants, minerals, sea, and animal products for treating more than 300 diseases. Traditional healers are facing lots of problem in the society at present. Social problems, family problems, personal problems, financial problems, political problems, decrease in the level of belief on traditional medicine, malpractice, and lack of recognition from the government are some of the problems faced by the traditional healers. Conclusion: Traditional medicines and healing systems are widely practiced in every community of Nepal. Large numbers of traditional healers are still actively continuing their indigenous and traditional medical knowledge and practices as a family tradition and culture. Understanding of diseases, definition, perception, diagnosis, treatment and use of local resources especially medicinal plants etc. may vary from one ethnicity to another and on the basis of topography. It can be concluded that traditional healers play an important role in their communities. They should be scientifically validated and integrated with traditional healing systems for protecting their intellectual property rights.